2018
DOI: 10.1021/acs.joc.7b02620
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Reaction of [60]Fullerene with Aroyl Compounds via Enolate-Mediated sp2 C–H Bond Activation and Hydroxylation

Abstract: A convenient and highly efficient palladium-catalyzed reaction of [60]fullerene (C) with aroyl compounds via enolate-mediated C-H activation and hydroxylation has been exploited for the first time to synthesize novel C-fused dihydrofurans, and rare 1,4-fullerenols. Further functionalization including etherification, and esterification of synthesized 1,4-fullerenols provided efficient access to versatile fullerene derivatives. Moreover, a plausible reaction mechanism leading to the observed products is proposed. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…15,16 In reaction of b-keto esters with C 60 different furan-fused fullerene derivatives were obtained. Enolatemediated C-H activation occurs in the presence of a base 17 usually with the aid of Cu(I)/Ag(I), 18,19 Pd(II)/Cu(II) mixtures, 20,21 Mn(III). 22 Recently, Gao and Chen described the synthesis of furan-fused fullerenes by controlling the addition sequence of base and iodine as oxidant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 In reaction of b-keto esters with C 60 different furan-fused fullerene derivatives were obtained. Enolatemediated C-H activation occurs in the presence of a base 17 usually with the aid of Cu(I)/Ag(I), 18,19 Pd(II)/Cu(II) mixtures, 20,21 Mn(III). 22 Recently, Gao and Chen described the synthesis of furan-fused fullerenes by controlling the addition sequence of base and iodine as oxidant.…”
Section: Resultsmentioning
confidence: 99%
“…This suggested that the formation mechanism of furano fullerenes could involve oxidative cycloaddition as described in the literature (Scheme 3). 17,18,20,23 With DBU b-keto ester 2 is deprotonated and enolate is formed which attacks C 60 affording anion 5. This anion goes through oxidation steps to afford radical 6, which undergoes intramolecular cyclization with the abstraction of hydrogen to give the nal product 3.…”
Section: Resultsmentioning
confidence: 99%
“…Although the complete fullerene molecular structure is relatively stable with strong capacity for absorbing free radicals, the rate of “capture” to free radicals is low. Functional fullerene derivative can substantially increase the rate of “capture” to free radicals, which ascribed to the modification of functional groups to destroy the conjugated structure of fullerenes. C 60 Cl 6 is a widespread precursor for the synthesis of highly functionalized fullerene derivatives. Many different nucleophiles can replace the chlorine atoms in C 60 Cl 6 to form multifunctional fullerene derivatives. In this study, C 60 Cl 6 as a precursor was applied to synthesize multifunctional fullerene derivatives via the reaction with aromatic amines (Scheme ), and its possibility as a propellant stabilizer was studied. We first explored the reactions of C 60 Cl 6 and aniline 1a .…”
Section: Results and Discussionmentioning
confidence: 99%
“…In this context, numerous 1,4-adducts with different functional groups have been synthesized. 4–9 Meanwhile, fullerene derivatives bearing sulfonamide groups have been proved as versatile platforms for the preparation of various functionalized fullerene compounds. 10 However, to the best of our knowledge, the direct synthesis of 1,4-(organo)(sulfonamide)[60]fullerenes from pristine C 60 remains unknown and very intriguing.…”
mentioning
confidence: 99%
“…On the other hand, the palladium-catalyzed difunctionalization of alkenes to incorporate two functional groups has emerged as a common and powerful tool in organic synthesis. 11 This method has also been applied to fullerene chemistry; 6,12–14 yet 1,4-difunctionalizations of fullerenes are rare. 6 Recently, we have been interested in developing new methodologies to functionalize fullerenes using palladium catalysts.…”
mentioning
confidence: 99%